Relationships matter : caregiver experience of contact/access planning practice and outcomes for permanency : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, New Zealand - Nielson-Vold, Kristin (Massey University, 2019)
When children are removed from parental care and placed out of home it is generally expected that birth family contact will occur. This commitment to birth family contact is based on beliefs about its psychological and emotional importance for children and is protected and enshrined in national and international policy. Literature clearly outlines, however, that birth family contact is one of the most complex and contested areas of practice for social workers and is often difficult for caregivers. This research set out to examine how caregivers in New Zealand experienced social worker practice in relation to contact planning. The aims of this research were to: critically explore caregivers’ experience of social work practice in regards to contact planning for children progressing to their permanent care; and identify processes and practices that were helpful for caregivers, pre-permanency, which supported quality outcomes post-permanency. To achieve these aims, a qualitative approach was utilised involving six semi-structured interviews of seven kin and non-kin caregivers. Research questions included: · How did caregivers’ experience social work practice in regards to contact planning? · What processes and practices were helpful for caregivers to support post-permanency outcomes? · What recommendations do caregivers have to improve quality contact outcomes post- permanency? A rather disheartening picture of social work contact practice emerged with caregiver experiences generally ranging from dissatisfying through to distressing. Several key findings were identified by caregivers in this research including, exclusion from decision-making processes, lack of information, limited support, lack of assessment, and limited relational practice by social workers. The findings of this research echo similar research both in New Zealand and internationally in relation to social work contact practices and the experiences of caregivers. Given this consistency of experience for caregivers, additional factors were examined to help provide explanations for the ongoing issues for caregivers, including organisational practice and culture. Recommendations were made which focused on contact experiences, assessment processes, training, policy, and the importance of relationship, to strengthen practice in this challenging area of work and improve caregiver experiences.
Keywords: Foster home care; New Zealand; Children; Institutional care; Foster children; Family relationships; Birthparents; Foster parents; Attitudes; 440901 Clinical social work practice